Microwave spectroscopy for diagnostics of nitrogen vacancy defects in diamond samples - Rudnicki, Daniel; Mrózek, Mariusz; Młynarczyk, Janusz; Gawlik, Wojciech (Photonics Letters of Poland, 2013)
A setup is described that combines microwave spectroscopy with optical excitation and detection of luminescence of NV- colour centers in diamond crystals. The parameters of the system (design of the microwave antenna, microwave power and timing, and fast optical detection) allow studies of relaxation properties of the NV- defects and manipulation of their spin properties. Full Text: PDF References Bradac, C., Gaebel, T. and Rabeau, J. R., Nitrogen-Vacancy Color Centers in Diamond: Properties, Synthesis, and Applications, in Optical Engineering of Diamond (eds R. P. Mildren and J. R. Rabeau), Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, Germany (2013). CrossRef C.-C. Fu, H.-Y. Lee, K. Chen, T.-S. Lim, H.-Y. Wu, P.-K. Lin, P.-K. Wei, P.-H. Tsao, H.-C. Chang, and W. Fann, "Characterization and application of single fluorescent nanodiamonds as cellular biomarkers", Proc. Natl. Acad. Sci. U.S.A. 104, 727 (2007). CrossRef P. Neumann, R. Kolesov, B. Naydenov, J. Beck, F. Rempp, M. Steiner, V. Jacques, G. Balasubramanian, M. L. Markham, D. J. Twitchen, S. Pezzagna, J. Meijer, J. Twamley, F. Jelezko, and J. Wrachtrup, "Quantum register based on coupled electron spins in a room-temperature solid", Nature Phys. 6, 249 (2010). CrossRef J. M. Taylor, P. Cappellaro, L. Childress, L. Jiang, D. Budker, P. R. Hemmer, A. Yacoby, R. Walsworth, and M. D. Lukin, "High-sensitivity diamond magnetometer with nanoscale resolution", Nature Phys. 4, 810 (2008). CrossRef N. R. S. Reddy, N. B. Manson, and E. R. Krausz, "Two-laser spectral hole burning in a colour centre in diamond", Journal of Luminescence 38, 46 (1987) CrossRef F. Jelezko, T. Gaebel, I. Popa, A. Gruber, and J. Wrachtrup, "Observation of Coherent Oscillations in a Single Electron Spin", Phys. Rev. Lett. 92, 076401 (2004) CrossRef